JUSTIFIKASI NORMATIF RECHTVINDING MELALUI ANALOGI MENGISI KEKOSONGAN HUKUM SYARAT SAH PERJANJIAN SMART CONTRACT - Agus Ridwan; Irwan Triadi (CV. ADIBA AISHA AMIRA, 2025)
The latest developments in Smart Contracts operating on Blockchain Technology have created a fundamental disruption to conventional contract law doctrines, resulting in a normative void (or regulatory gap) within the positive law of Indonesia. Indonesian Civil Law (KUHPerdata) and the ITE Law (Law on Information and Electronic Transactions) have not explicitly regulated the legal consequences of technical failure (code bugs) or unlawful purpose in autonomously executed agreements (self-executing code). This research aims to analyze the normative justification for judges and formulate a classification of legal consequences for Smart Contract disputes. This study employs Normative Legal Research (Yuridis Normatif), utilizing the Statutory Approach and the Conceptual Approach.